Combination ergotamine and caffeine improves seated blood pressure and presyncopal symptoms in autonomic failure - Arnold, Amy C.; Ramirez, Claudia E.; Choi, Leena; Okamoto, Luis E.; Gamboa, Alfredo; Diedrich, André; Raj, Satish R.; Robertson, David; Biaggioni, Italo; Shibao, Cyndya A. (Frontiers in Physiology, 2014)
Severely affected patients with autonomic failure require pressor agents to counteract the blood pressure fall and improve presyncopal symptoms upon standing. Previous studies suggest that combination ergotamine and caffeine may be effective in the treatment of autonomic failure, but the efficacy of this drug has not been evaluated in controlled trials. Therefore, we compared the effects of ergotamine/caffeine on seated blood pressure and orthostatic tolerance and symptoms in 12 primary autonomic failure patients without history of coronary artery disease. Patients were randomized to receive a single oral dose of placebo, midodrine (5-10 mg), or ergotamine and caffeine (1 mg and 100 mg, respectively) in a single-blind, crossover study. Blood pressure was measured while patients were seated and after standing for up to 10 minutes, at baseline and at 1 hour post-drug. Ergotamine/caffeine increased seated systolic blood pressure, the primary outcome, compared with placebo (131±19 and 95±12 mmHg, respectively, at 1 hour post-drug; p=0.003 for time effect). Midodrine also significantly increased seated systolic blood pressure (121±19 mmHg at 1 hour post-drug; p=0.015 for time effect versus placebo), but this effect was not different from ergotamine/caffeine (p=0.621). There was no significant effect of either medication on orthostatic tolerance; however, ergotamine/caffeine improved presyncopal symptoms (p=0.034). These findings suggest that combination ergotamine and caffeine elicits a seated pressor response that is similar in magnitude to midodrine, and improves symptoms in autonomic failure. Thus, ergotamine/caffeine could be used as an alternate treatment for autonomic failure, in carefully selected patients without comorbid coronary artery disease.